2017
DOI: 10.5539/elt.v10n3p101
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Errors in Written English Sentences: A Case Study of Thai EFL Students

Abstract: The purposes of the present study were to examine the language errors in a writing of English major students in a Thai university and to explore the sources of the errors. This study focused mainly on sentences because the researcher found that errors in Thai EFL students' sentence construction may lead to miscommunication. 104 pieces of writing written by 26 second-year English major students who enrolled in the Writing II course were collected and analyzed. Results showed that the most frequently committed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
126
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 14 publications
18
126
2
2
Order By: Relevance
“…Writing in the English language has been considered a difficult skill for EFL students to master because this group of students rarely has a chance to write in English (Kim & Kim, 2005;Kongsuebchart & Suppasetseree, 2015;Sermsook et al, 2017). Consequently, producing an error-free piece of English writing is a challenging task for them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Writing in the English language has been considered a difficult skill for EFL students to master because this group of students rarely has a chance to write in English (Kim & Kim, 2005;Kongsuebchart & Suppasetseree, 2015;Sermsook et al, 2017). Consequently, producing an error-free piece of English writing is a challenging task for them.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, producing an error-free piece of English writing is a challenging task for them. A great number of studies in the field of second language acquisition (SLA) and Error Analysis (EA) reveal that EFL students' written work contains various types of errors (Huang, 2006;Rattanadilok Na Phuket & Othman, 2015;Sermsook et al, 2017;Zafar, 2016;Zheng & Park, 2013). Among those errors, grammatical ones can pose serious difficulties for EFL students since the grammatical rules of English and those of their native language are relatively different (Nonkukhetkong, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the process based writing approach since initiative writing, preparing draft, reviewing and arranging processes are used it is possible to develop the grammar skills of the students who are exposed to significant and related feedback systematically (Cuéllar, 2013). In addition well performed grammar and word teaching will help students improve their writings (Sermsook, Liamnimitr & Pochakorn, 2017). The students who acquire skills of words and forming sentences provide transferring what they learn to daily life using them especially in writing activities.…”
Section: Findings / Resultsmentioning
confidence: 99%
“…Based on the discussion of the findings, it is concluded that Indonesian students in this study committed a great number of errors due to first language transfer. Sermsook (2017) conducted a similar research with the purposes of examining the language errors in a writing of English major students in a Thai university and exploring the sources of the errors. Their study discovered that punctuation, articles, subject-verb agreement, spelling, capitalization, and fragment as the most frequently committed errors respectively.…”
Section: Previous Studiesmentioning
confidence: 99%